“Calcu-less craze”: an online gamified approach to mathematics learning - Mohamad Hanafi, Nurfatihah; Hassan, Suraya; Hisham, Balqis; Md Saad, Norlaili; Happas, A'fifah (Asian Scholars Network, 2025)
Abstract: This research explores the efficacy of an online mathematics game as a tool to enhance learning outcomes in mathematical education. The game, designed to leverage the interactive and immersive nature of online gaming, offers a dynamic platform for learners to engage with mathematical concepts in a playful and stimulating environment. Therefore, an educational online game for Calculus has been developed called as “Calcu-less Craze” which focuses on differentiation and integration topics. This study aims to examine the impact of online game-based learning activities on the students’ perceptions towards Calculus subject. A sample of 100 students taking Mathematics 3 (MAT0134) from CFS IIUM has been selected for this pilot study using purposive sampling technique. SPSS 28.0 was used to analyze the data using both descriptive and inferential statistics. The result suggested that students playing “Calcu-less Craze” may enhance their learning in mathematics. In summary, the transformative potential of an online mathematics game as a catalyst for enhancing learning experiences and outcomes in mathematical education. This opens the door for creative methods to teaching and learning in the digital age.